2023
DOI: 10.1038/s41556-022-01055-y
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic cancer cells upregulate LPAR4 in response to isolation stress to promote an ECM-enriched niche and support tumour initiation

Abstract: Publisher's note Springer Nature remains neutral with regard to jurisdictional claims in published maps and institutional affiliations.Springer Nature or its licensor (e.g. a society or other partner) holds exclusive rights to this article under a publishing agreement with the author(s) or other rightsholder(s); author self-archiving of the accepted manuscript version of this article is solely governed by the terms of such publishing agreement and applicable law.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…Their findings revealed that the adaptation of cancer stem cells to suboptimal niche environments protects them from chemotherapy and identifies a candidate cell of origin of relapse after treatment in CRC that they called HRC. Similar findings have been obtained by Wu C. from the Sara M. Weis and David A. Cheresh group, studying how microenvironmental stresses affect tumor initiation and progression of aggressive pancreatic cancer cells [ 44 ]. These authors have recently reported that the harsh microenvironments of the body can push certain pancreatic cancer cells to overcome the stress of being isolated and make them more adept at initiating and forming new tumor colonies.…”
Section: Discussionsupporting
confidence: 83%
“…Their findings revealed that the adaptation of cancer stem cells to suboptimal niche environments protects them from chemotherapy and identifies a candidate cell of origin of relapse after treatment in CRC that they called HRC. Similar findings have been obtained by Wu C. from the Sara M. Weis and David A. Cheresh group, studying how microenvironmental stresses affect tumor initiation and progression of aggressive pancreatic cancer cells [ 44 ]. These authors have recently reported that the harsh microenvironments of the body can push certain pancreatic cancer cells to overcome the stress of being isolated and make them more adept at initiating and forming new tumor colonies.…”
Section: Discussionsupporting
confidence: 83%
“…As a poor prognostic indicator, FAK was able to drive desmoplasia, immunosuppression, and metastasis of PDAC by regulating the expression of matrix metalloproteinases (MMP), PI3K/AKT, and other signals [ 184 , 185 ]. A recent study uncovered that PDAC cells exposed to environmental stress or chemotherapy could induce fibronectin expression by up-regulating lysophosphatidic acid receptor 4 (LPAR4), promoting an ECM-enriched niche and therapeutic resistance [ 186 ]. MMPs, over-expressed mainly by CAFs, are thought to lead to massive breakdown of the ECM, neovascularization, tumor spread, and metastasis.…”
Section: More Complete Immunophenotyping: Enrolling the Matrixmentioning
confidence: 99%
“…The mesenchymal cells enriched in the later disease stages exhibit higher expression of FN1 and stemness-associated genes 64 . Additionally, an independent study found that the interaction between integrins and tumour-deposited fibronectin is involved in the niche-induced cancer cell stemness 65 . The CXCL14 gene encodes a member of the CXC chemokine family whose role in the PDAC is relatively unexplored.…”
Section: Fig 5: Transcriptional Profile Of Triple-high Cells a Umap V...mentioning
confidence: 99%